Prevalence of the major diseases in Penaeus vannamei farmen of Sinaloa Mexico. / Prevalencia De Las Principales Enfermedades En Penaeus Vannamei De Cultivo En Sinaloa, Mexico - Morales-Covarrubias, María Soledad; García-Aguila, Noemí; Bolan-Mejía, María del Carmen; Zamora García, Oscar Guillermo (Revista Científica de la Facultad de Ciencias Veterinarias, 2020)
ABSTRACT The aim of this study was to determine the prevalence and severity of the diseases: acute hepatopancreatic necrosis disease (AHPND), necrotizing hepatopancreatitis (NHPB) caused by intracellular bacterium (Hepatobacter penaei), septic hepatopancreatic necrosis (NHPS), and the white spot syndrome virus (WSSV) in farmed shrimp during two productive cycles (spring and summer) in the years (yrs) 2016 and 2017. From 360 studied shrimps, 90% showed external characteristics of apparently healthy animals, while only 10% of the specimens presented red coloration, soft cuticle, and muscular opacity. AHPND was the disease with the higher average prevalence for all the studied zones and seasons, with a prevalence of 53.33% in 2016 and 60.16% in 2017, followed by NHPS with 36.66% in 2016 and 42.83% in 2017. The incidence of WSSV was the lowest compared to the other diseases studied in this work, with 16.16% in 2016 and 20% in 2017; NHPB was only observed in summer with an average prevalence of 16.16% for both yrs. The northern area of Mexico registered the highest rates of mortality associated to these diseases, excluding WSSV, which resulted in being the most prevalent disease in the southern area (although such difference it is not statistically significant). The specimens diagnosed with AHPND exhibit severe damage in hepatopancreas as well as cellular detachment in the intestinal proximity. The organisms with NHPS showed multifocal cellular detachment in hepatopancreas and bacteria growth in heart, gills, lymphoid organ, connective tissue and muscles. The physicochemical variables considered for this study did not show significant variability among the zones and seasons analyzed, however, any alteration on these parameters might cause stress in the shrimps impairing the immune response against opportunistic pathogens. The presence of bacterial and viral diseases identified in this work is likely related to a low quality of the post-larvae, or an inadequate farming environment.RESUMEN El objetivo del presente estudio fue determinar la prevalencia y severidad de las enfermedades Necrosis Aguda del Hepatopáncreas (AHPND), Necrosis del Hepatopáncreas (NHPB) causado por bacterias intracelulares (Hepatobacter penaei) , bacteriosis (NHPS) y el virus de la mancha blanca (WSSV), en camarones de cultivo durante dos ciclos (primavera y verano) en los años 2016 y 2017. Los resultados de los 360 camarones colectados mostraron características externas de animales aparentemente sanos (90%) y 10% con coloración rojiza, cutícula suave y opacidad muscular. AHPND fue la enfermedad con mayor prevalencia promedio para todas las zonas y temporadas con 53,3% en 2016 y 60,6% en 2017, seguida de NHPS con 36,66% en 2016 y 42,3% en 2017. La prevalencia de WSSV fue baja respecto a las demás con 16,16% en 2016 y 20% en 2017. NHPB se presentó en verano con prevalencias de 16,6 para 2016 y 2017. La zona norte presentó la mayor prevalencia de las enfermedades excluyendo a WSSV, misma que obtuvo una prevalencia mayor en la zona sur que en las demás zonas (sin embargo, dicha diferencia no es estadísticamente significativa). Los organismos con AHPND presentaron daños severos en hepatopáncreas con desprendimiento celular de la región proximal al intestino y NHPS con desprendimiento celular multifocal en hepatopáncreas y presencia de colonias de bacterias en corazón, branquias, órgano linfoide, tejido conectivo, musculo y ciegos hepáticos. Los parámetros fisicoquímicos en este trabajo no tuvieron diferencias significativas entre zonas en cada temporada, sin embargo, la alteración de alguno de ellos ocasiona estrés en los camarones, reduciendo la actividad anti-patógenos oportunistas. La presencia de las enfermedades bacterianas y virales identificadas en este trabajo probablemente estuvieron relacionadas con la calidad de la postlarva, o por un inadecuado ambiente de cultivo, propiciado por acumulación de materia orgánica